(untitled) (Security Dialogues, 2023)
The uniqueness of each system stems from the fact that the risks of disasters arespecific and that their presence and manifestation are not universal and the same for everycountry. Just as no country is the same in all other segments, their disaster risk systems areunequal. The paper describes the systems in four different countries, through observationand comparison of four areas of activity that are implemented in dealing with disasters.First of all, in the paper, the legal basis and institutional frameworks on which these systemsrest in each of the countries were considered – starting from the international level andguidelines given at international conferences, to all by-laws and local disaster activity plans.It was considered how each of the states implements risk mitigation activities and how itincreases preparedness for them. When the system recognizes risks, their probability andthe frequency of their occurrence, activities are planned to prepare the country and everyindividual in it for a potentially unwanted event. Differences in the ways of mitigating risksand preparing all elements of the system and protected values for disasters are presented. The third element of action in the event of disasters concerns the response. In this segment,questions are raised regarding institutional solutions in the system, division of responsibilities,the priority of response and mobilization of resources at all levels. The last phase, the onethat occurs after the disaster, and that is the recovery from it, depends on the reaction.In the paper, it was discussed how in the end, when a disaster occurs and when damageto the population, environment, material and other goods occurs, how each of the statesimplements reconstruction, i.e. how it recovers - whether that recovery was previously wellplanned or whether ad hoc solutions are applied.